THE APPLICATION OF PEER COUNSELING IN EXTRACURRICULAR ACTIVITIES AS AGENTS OF CHANGE IN IMPROVING ASSERTIVENESS IN VICTIMS OF BULLYING AT SMP NEGERI 1 SUNGGUMINASA - Nuraisya, Nuraisya; Pandang, Abdullah; Buchori, Sahril (Jurnal Konseling Pendidikan Islam, 2025)
The application of peer counseling through the Change Agent extracurricular program in increasing assertiveness among bullying victims at SMP Negeri 1 Sungguminasa. The background of this research is based on the rising cases of bullying in school environments, which negatively impact students' mental health and social development. The method used is a quasi-experimental approach with a pretest-posttest control group design. The research sample consists of 30 students identified as bullying victims, divided into experimental and control groups. The results show that the assertiveness level of students before the implementation of peer counseling was in the low category; however, after the intervention, there was a significant increase in the experimental group. Hypothesis testing using a t-test revealed a significance value (p < 0.05), indicating that peer counseling effectively enhances students' assertiveness. This study concludes that the implementation of peer counseling in the Change Agent extracurricular program can be an effective alternative to address bullying issues and improve students' self-confidence in schools. It is hoped that the findings of this research can contribute to the development of guidance and counseling programs in schools and raise awareness of the importance of assertiveness among students.